2006
DOI: 10.1038/sj.emboj.7601448
|View full text |Cite
|
Sign up to set email alerts
|

Novel TRF1/BRF target genes revealed by genome-wide analysis of Drosophila Pol III transcription

Abstract: Metazoans have evolved multiple paralogues of the TATA binding protein (TBP), adding another tunable level of gene control at core promoters. While TBP-related factor 1 (TRF1) shares extensive homology with TBP and can direct both Pol II and Pol III transcription in vitro, TRF1 target sites in vivo have remained elusive. Here, we report the genome-wide identification of TRF1-binding sites using high-resolution genome tiling microarrays. We found 354 TRF1-binding sites genome-wide with B78% of these sites displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…2B, lane 9), but depletion of TBP had no discernable effect (compare lanes 7 and 8). This agrees with findings by others that TRF1 is required for tRNA transcription in D. melanogaster (17,18). Altogether, these results, along with the ChIP results shown in Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…2B, lane 9), but depletion of TBP had no discernable effect (compare lanes 7 and 8). This agrees with findings by others that TRF1 is required for tRNA transcription in D. melanogaster (17,18). Altogether, these results, along with the ChIP results shown in Fig.…”
Section: Resultssupporting
confidence: 82%
“…In contrast, however, our data revealed that TBP is significantly more enriched than TRF1 at U6 promoters. These latter findings are consistent with the failure to detect TRF1 at U6 promoters in genome-wide ChIP-on-chip experiments performed by Isogai et al (18). Furthermore, immunodepletion of TBP (but not TRF1) from a nuclear extract greatly inhibited U6 transcription in vitro (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…10). TRF1, which is largely involved in RNA polymerase III transcription in Drosophila (Takada et al 2000;Isogai et al 2007b), has little or no effect on transcription of DPE-containing or TATA-containing genes. TRF2 is important for both DPE-mediated and TATA-mediated transcription.…”
Section: A Genetic Circuit In Which Mot1 and Nc2 Oppose Tbp To Contromentioning
confidence: 99%
“…At all these genes, binding of Pol III correlates with gene activity as measured by RNA levels. In Drosophila Schneider line 2 (S2) cells, a recent analysis has identified 359 BRF1 and 354 TRF1 (which replaces TBP in Drosophila TFIIIB) genomic binding sites, corresponding mostly to tRNA genes, as well as to other RNA genes such as the RN7SL1 (7SL) RNA gene and some snoRNA genes (Isogai et al 2007). In mammalian cells, genomewide studies have been limited by the lack of a technology to study repeated sequences.…”
mentioning
confidence: 99%